Melioidosis A Serious Emerging Threat in Bangladesh - Das, Aparna; Ahasan, H A M Nazmul; Minnat, Baharul; Singha, Chayan Kumar (Journal of Medicine, 2014)
Melioidosis, a pyogenic infection that presents acutely or as a chronic infection, is caused by the soilassociated bacterium Burkholderiapseudomallei. Infection is acquired by inoculation or inhalation and is more common in patients with underlying chronic disease. It is endemic in the tropical belt. Although Bangladesh is not considered as a country where melioidosis is endemic, an increasing number of cases have been reported recently. Definitive diagnosis requires the isolation of B. pseudomalleiin culture from clinical specimens. However, the laboratory diagnosis of melioidosis in Bangladesh and other under-resourced countries is limited by a lack of familiarity with the bacterium and a lack of facilities to accurately confirm the identity of the isolate. It is highly likely that melioidosis is underdiagnosed in this country. There is a need to increase awareness of this infection among clinicians and clinical microbiologists and improve laboratory facilities for the selective isolation and accurate identification of B. pseudomallei. Melioidosis has a notoriously protracted course; cure is difficult without a prolonged course of appropriate antibiotics. DOI: http://dx.doi.org/10.3329/jom.v14i2.19669 J Medicine 2013, 14(2): 164-173